Symbiotic bacteria-mediated imbalance and repair of immune homeostasis: exploring novel mechanisms of microbiome-host interactions in atopic dermatitis - Lai, Xingyue; Huang, Jilin; Li, Yulin; Dong, Liang (Frontiers in Immunology, 2025)
The skin surface is colonised by a rich microbiome, and intricate interactions between this microenvironment and microbial communities are critical for maintaining skin homeostasis. Atopic dermatitis (AD), a chronic inflammatory skin disease characterised by skin barrier dysfunction and aberrant immune activation, exhibits a rising global incidence. While conventional therapeutic strategies offer short-term symptom control, their long-term use is limited by adverse effects including skin atrophy, metabolic disorders, and increased infection risk. Critically, these approaches fail to cure AD or reverse the underlying immune imbalance. Recent research has firmly established the skin microbiome as a central driver in AD pathogenesis. The molecular mechanisms underpinning microbiome-host interactions, including the potential for remote regulation via the gut-skin axis, are now being actively investigated. This review systematically analyses how microbial dysbiosis in AD promotes Th2/Th17 immune polarization through three key pathways: microbial metabolites, immune signalling, and barrier integrity. Building on these mechanistic insights and recent advances, we propose novel multimodal therapeutic strategies targeting the microbial-immune axis. We further elucidate the role of commensal bacteria in maintaining immune homeostasis. Ultimately, this synthesis aims to bridge fundamental research with clinical applications, providing a robust theoretical foundation for future therapeutic development and clinical studies in AD management.